Pediatric Acute Lymphoblastic Leukemia: Efficacy and safety of recombinant E. coli-asparaginase in infants (less than one year of age) with acute lymphoblastic leukemia - van der Sluis, Inge (Ferrata Storti Foundation, 2013)
The pharmacokinetics, pharmacodynamics, efficacy and safety of a new recombinant E. coli-asparaginase preparation were evaluated in infants (<1 year of age) with de novo acute lymphoblastic leukemia. Twelve patients were treated according to the INTERFANT-06 protocol and received up to 10,000 U/m(2) recombinant asparaginase as intravenous infusions on days 15, 18, 22, 25, 29 and 33 of remission induction treatment. The asparaginase dose was individually adjusted by protocol to 67% of the calculated dose for infants <6 months, and to 75% of the calculated dose for infants aged 6–12 months. The trough serum asparaginase activities observed were above 20, 50, and 100 U/L in 86%, 71%, and 51% of measured samples, respectively. Looking only at the data assessed 3 days after asparaginase infusion these percentages were 91%, 84%, and 74%, respectively. Asparagine was completely depleted in serum in all but one patient who was the youngest in the study. No anti-asparaginase antibodies were detected during this treatment phase. Observed adverse reactions are known to be possible and are labeled side effects of asparaginase treatment and chemotherapy. We conclude that the asparaginase dose regimen used in infants is safe and provides complete asparagine depletion for the desired time period in nearly all patients. Measured asparaginase trough serum levels justify the higher doses used in infants compared to in older children and show that 3-day intervals are preferred over 4-day intervals. (This trial was registered at www.clinicaltrialsregister.eu as EudraCT number 2008-006300-27).